A elaboraçao de projetos de desenvolvimento territorial na Serra do Brigadeiro, Brasil - Freitas, Alan Ferreira de (2016)
The purpose of this article is to analyze the territorial projects developed in the Territory of Serra do Brigadeiro, Minas Gerais, in the period 2003-2010, in order to identify their characteristics and contributions for innovations in rural development concepts. The different types of investment and the perception of territorial actors about projects and concepts of development that underlies the projects were analyzed. We conclude that the notion of rurality, strongly oriented by a sectorial bias, was influenced by the institutional framework created by politics, resulting in the elaboration of projects for education, cooperative services, and local cultural aspects, transcending the prevailing sense of economic development. This context indicates the existence of a social dynamics influenced by new references to the promotion of rural development.